2018
DOI: 10.1177/1471301218784806
|View full text |Cite
|
Sign up to set email alerts
|

The participation of people with dementia in the planning of their care and support: An integrative literature review

Abstract: Background People with dementia continue to voice concerns that health professionals are reluctant to engage with them about the planning of their care and support. Instead, their perspective is that such plans are often made by others and fail to reflect their wishes. Objective This review aimed to examine investigations of the participation of people living with dementia in the planning of their care and support, when they have also provided study data. Methods An integrative literature review was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Another literature review identified few studies that involved persons with dementia in planning their own care and support [ 68 ]. The lack of active and meaningful involvement of persons with dementia in shaping policies and interventions that impact their care and quality of life has been recognized as a problem [ 69 , 70 ]. Therefore, future research on what constitutes PCCS for dementia must include those with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Another literature review identified few studies that involved persons with dementia in planning their own care and support [ 68 ]. The lack of active and meaningful involvement of persons with dementia in shaping policies and interventions that impact their care and quality of life has been recognized as a problem [ 69 , 70 ]. Therefore, future research on what constitutes PCCS for dementia must include those with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, families and persons living with dementia expressed the desire to be engaged and to be supported with respect to intimacy and sexual expression. When we consider the significant role of family members in decision-making regarding even the most intimate aspects of residents’ lives, and the importance of engaging persons living dementia about their own care ( Read et al, 2020 ), this limited engagement is concerning.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also suggest that more attention is needed to foster investment in and engagement with the intervention. Having strong local leadership is a well-established component of implementation strategies, 165 yet was not achieved in all sites. Specifically, building relationships with local geriatricians may be one way of increasing buy-in in the MDTs while also providing local leadership.…”
Section: Factors Influencing Implementation Of the Interventionmentioning
confidence: 99%